Customer expectations regarding packaging of food products in e-commerce in Hungary - Póka, Viktor (Studia Mundi – Economica, 2023)
The aim of the study is to highlight on the negative ecological impacts caused by online commerce, which are directly proportional to the increasing number of orders. The previously thriving e-commerce sector saw further strengthening from 2020 onwards due to responses to the COVID-19 pandemic. However, this growth also brought about numerous negative externalities, as customers ordered from various retailers, deliveries were handled by different couriers, and supply chains often spanned multiple continents. This also meant that logistical processes imposed significant burdens on the environment, including shipping and the strain caused by packaging materials. Simultaneously, the number of consumers who expect 'green solutions' from service providers has increased. They take this into consideration during their purchases and are even willing to pay more for a product or service that demonstrates sustainability efforts. The study presents the challenges posed by packaging materials in the field of e-commerce. Through the analysis of the available questionnaire, we can gain insights into whether expectations regarding eco-friendly packaging solutions correlate with consumers' educational background, income level, place of residence, age, and gender.
Keywords: E-commerce; Packaging; Sustainability